2021
DOI: 10.3390/su13020730
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style in Amateur Club Sports: A Key Element in Strategic Management

Abstract: Leadership is key in sports management, as it allows organizations to endure over time. Leadership style determines how an organization or sports club works. The purpose of this study is to investigate employees’ perceptions of the leadership style of presidents (managers) in amateur clubs and how it influences the effort, efficiency and satisfaction of those employees. The sample consists of club managers (N = 334), of whom 286 are men and 48 are women, with an average age of 42.05 (±9.64). The subordinate ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…Moreover, the research has proved that sport organizations run by transformational leaders achieve organizational goals, teamwork and organizational excellence (Lasrado and Kassem, 2021). Furthermore, it has been demonstrated that transformational leadership has a significant effect on the organizational learning process and on organizations' commitment to change through the improvement of innovation, performance and competitiveness in the service sector like sport services firms (Martínez-Moreno et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the research has proved that sport organizations run by transformational leaders achieve organizational goals, teamwork and organizational excellence (Lasrado and Kassem, 2021). Furthermore, it has been demonstrated that transformational leadership has a significant effect on the organizational learning process and on organizations' commitment to change through the improvement of innovation, performance and competitiveness in the service sector like sport services firms (Martínez-Moreno et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Leadership also plays a vital role in the success of SM-related initiatives. The leadership style is considered vital for successful strategic management implementation (Martínez-Moreno et al, 2021). Martínez-Moreno et al (2021) applied the four identified leadership styles (traits and roles of the leader, situational, transformational, transactional) to sports organizations.…”
Section: Strategic Management -Leadership Csfsmentioning
confidence: 99%
“…The leadership style is considered vital for successful strategic management implementation (Martínez-Moreno et al, 2021). Martínez-Moreno et al (2021) applied the four identified leadership styles (traits and roles of the leader, situational, transformational, transactional) to sports organizations. Recent research efforts have combined the aforementioned two concepts (strategic management and leadership) and advocate that the leadership style and approach are considered key elements for successful strategic management in SM (Martínez-Moreno et al, 2021).…”
Section: Strategic Management -Leadership Csfsmentioning
confidence: 99%
“…The leadership style is considered vital for successful strategic management implementation(Martínez-Moreno et al, 2021) Martínez-Moreno et al (2021). applied the four identified leadership styles (traits and roles of the leader, situational, transformational, transactional) to sports organizations.…”
mentioning
confidence: 99%
“…applied the four identified leadership styles (traits and roles of the leader, situational, transformational, transactional) to sports organizations. Recent research efforts have combined the aforementioned two concepts (strategic management and leadership) and advocate that the leadership style and approach are considered key elements for successful strategic management in SM(Martínez-Moreno et al, 2021). sports sponsorship has been a research issue in SM in the last decades Koronios et al (2021).…”
mentioning
confidence: 99%